A hydrophobic, oil-resistant, degradable lignin-based waterborne polyurethane for paper coating and a preparation method thereof

CN117924641BActive Publication Date: 2026-10-30SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410066502.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-17
Publication Date
2026-10-30
Estimated Expiration
2044-01-17

AI Technical Summary

Technical Problem

Kumar等(Progress in Organic Coatings,2023,176,107386)将丙烯酸改性的环氧大豆油涂在纸张表面,采用光固化的方式获得高度交联的纸张涂层,涂覆后的纸张吸水性大幅降低,耐油性提高,然而丙烯酸改性的环氧大豆油价格昂贵,限制其工业化应用

Benefits of technology

[0022]1.本发明采用反应活性高的低分子量木质素合成水性聚氨酯,木质素和聚氨酯基体间有良好的相容性和强的氢键作用,木质素也起到了交联剂的作用,因此获得了力学性能优异的水性聚氨酯。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004668293460000041
    Figure BDA0004668293460000041
Patent Text Reader

Abstract

The application discloses a hydrophobic oil-resistant degradable lignin-based waterborne polyurethane for paper coating and a preparation method thereof. The lignin-based waterborne polyurethane is obtained by reaction of the following components in parts by mass: polyester diol 60-90 parts, low-molecular-weight lignin 10-40 parts, hydrophobic modifier 1-10 parts, isocyanate 25-50 parts, anionic hydrophilic chain extender 4-8 parts, catalyst 0.2-0.6 parts, and neutralizing agent 3-6 parts. The high reactivity and multifunctionality of the low-molecular-weight lignin are utilized to construct a chemical crosslinking network, which greatly improves the mechanical properties of the waterborne polyurethane. A small amount of hydrophobic modifier is introduced to improve the hydrophobic properties of the lignin-based waterborne polyurethane. The waterborne polyurethane is coated on the surface of paper to improve the hydrophobic oil resistance of the paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waterborne polyurethane materials technology, specifically relating to a hydrophobic, oil-resistant, and biodegradable lignin-based waterborne polyurethane for paper coating and its preparation method. Background Technology

[0002] While plastic packaging has made life more convenient, it has also caused serious white pollution and consumed a large amount of petrochemical resources. Therefore, countries around the world have successively introduced policies to restrict plastic use. In January 2020, the National Development and Reform Commission and the Ministry of Ecology and Environment issued the "Opinions on Further Strengthening the Governance of Plastic Pollution," which clearly stated: orderly prohibition and restriction of the production, sale, and use of certain plastic products, active promotion of alternative products, and standardized recycling of plastic waste.

[0003] Paper-based packaging materials are a promising green packaging material, having partially replaced existing plastic packaging in the disposable consumer goods sector. However, paper-based materials suffer from poor water resistance, poor resistance to greases, and poor gas barrier properties, necessitating modification. A common method is to laminate paper and plastic at high temperatures to prepare paper-plastic composites, using plastics such as polyethylene, polypropylene, and polyethylene terephthalate. Another method involves coating the paper surface with emulsion resins, such as waterborne polyurethane emulsions, polyacrylic acid resins, and styrene-butadiene latex. For example, patent CN114634610A discloses a waterborne polyurethane and its preparation method, which exhibits good adhesion to paper while improving the paper's heat resistance, water resistance, and tear resistance. Wanhua Chemical disclosed a polyacrylic acid emulsion for paper coating and its preparation method (CN116265502A), which produces a coating with excellent anti-stick properties. Recently, BASF disclosed a styrene-butadiene polymer latex (CN114901707A) for use as a paper coating adhesive, which exhibits excellent wet friction and peel properties. While these coatings improve the performance of paper-based packaging materials, they are all derived from petrochemical resources, are non-renewable, and difficult to recycle, still contributing to white pollution and hindering the biodegradability of paper.

[0004] In recent years, the use of biomass to synthesize polymer materials has become a research hotspot. This not only reduces the consumption of petroleum-based raw materials but also endows polymer materials with biodegradable properties. Utilizing biomass to prepare biomass-based coatings suitable for paper-based packaging materials is of great significance. Common biomass materials include starch, chitosan, cellulose, vegetable oil, and lignin. Kumar et al. (Progress in Organic Coatings, 2023, 176, 107386) coated acrylic acid-modified epoxidized soybean oil onto the surface of paper and obtained a highly cross-linked paper coating using photocuring. The coated paper exhibited significantly reduced water absorption and improved oil resistance. However, the high price of acrylic acid-modified epoxidized soybean oil limits its industrial application. Kong et al. (Coatings, 2021, 11, 192) modified lignin with vinyl chloroacetate and copolymerized the modified lignin with vinyl acetate to obtain a lignin / vinyl acetate copolymer, which was used as a paper coating. Although the tensile strength and water resistance of the paper were improved, acetone was used as a solvent during the sizing process, which is neither green nor environmentally friendly. Patent CN116856196A discloses a method for preparing a fully bio-based oleophobic and hydrophobic paper surface coating and its application. Using natural monophenols and glycidyl dimerase as raw materials, a fully bio-based monophenol-grafted glycidyl dimerase is prepared through ring-opening etherification as a paper oleophobic and hydrophobic surface coating. However, this coating requires acetone solvent during sizing and still exhibits poor water resistance. Xie et al. (International Journal of Biological Macromolecules, 2021, 189:690-697) synthesized a lignin-based polyurethane containing silver ions with antibacterial function, which was used as a paper coating, improving the mechanical properties and water resistance of the paper. However, its synthesis requires the use of high-boiling-point organic solvents, causing environmental harm. Therefore, developing an industrially scalable, hydrophobic, oleophobic, and biodegradable biomass-based paper coating is a significant challenge. Summary of the Invention

[0005] To address the problems of existing technologies, the primary objective of this invention is to provide a hydrophobic, oil-resistant, and biodegradable lignin-based waterborne polyurethane for paper coating. The waterborne polyurethane, by weight, comprises: 60-90 parts polyester diol, 10-40 parts low molecular weight lignin, 1-10 parts hydrophobic modifier, 20-50 parts isocyanate, 4-8 parts anionic hydrophilic chain extender, 0.2-0.6 parts catalyst, and 3-6 parts neutralizer. The total amount of polyester polyol and low molecular weight lignin is 100 parts, and the isocyanate index R (the ratio of -NCO / -OH) is 1.0-1.2, more preferably 1.1.

[0006] Preferably, the polyester diol is at least one of polycaprolactone diol (PCL), polylactic acid diol (PLA), and poly(lactide-co-caprolactone) diol, with a number-average molecular weight of 500 to 5000 g / mol.

[0007] Preferably, the low molecular weight lignin is lignin obtained by extraction with ethanol, acetone or ethyl acetate using industrial lignin with a weight average molecular weight of 3000-6000 g / mol as raw material, and its weight average molecular weight is 800-1500 g / mol.

[0008] Preferably, the hydrophobic modifier is at least one of double-hydroxyl-terminated polydimethylsiloxane, single-hydroxyl-terminated polydimethylsiloxane, and single-double-hydroxyl-terminated polydimethylsiloxane, with a number-average molecular weight of 1000-5000 g / mol.

[0009] Preferably, the isocyanate is at least one selected from isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), and toluene diisocyanate (TDI).

[0010] Preferably, the anionic hydrophilic chain extender is at least one of 2,2-dimethylolpropionic acid (DMPA) and 2,2-dimethylolbutyric acid (DMBA).

[0011] Preferably, the catalyst is an organotin catalyst.

[0012] The neutralizing agent is at least one of triethylamine and ammonia.

[0013] Another object of the present invention is to provide a method for preparing the above-mentioned hydrophobic, oil-resistant, and biodegradable lignin-based waterborne polyurethane for paper coating, the method comprising the following steps:

[0014] (1) After dehydrating the polyester diol and hydrophobic modifier under vacuum at 110±10℃, the temperature is lowered to 70~90℃; under nitrogen protection, isocyanate and catalyst are added and reacted for 1~2 hours; then anionic hydrophilic chain extender is added and reacted for 1~2 hours; low molecular weight lignin is added and reacted for 2~5 hours. Acetone is added during the reaction to reduce the viscosity of the system; after the reaction is completed, the temperature is lowered to room temperature, a neutralizing agent is added, and the mixture is stirred for 0.5~1 hour.

[0015] (2) Add deionized water to the above system at a speed of 1000-2000 r / min, control the solid content of the emulsion to be 20-45 wt%, continue stirring for 5-10 minutes after emulsification, and then adjust the speed to 300-500 r / min and continue stirring for 0.5-1 hour; perform vacuum distillation on the emulsified sample at 40-60℃ and vacuum degree less than -0.09 MPa to remove acetone and obtain the lignin-based waterborne polyurethane.

[0016] Preferably, the anionic hydrophilic chain extender is added in solution form with a concentration of 20-30 wt%, and the solvent is one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

[0017] The low molecular weight lignin is added in the form of a solution with a concentration of 10-30 wt% and acetone as the solvent.

[0018] Preferably, in step (1), the amount of acetone added during the reaction is 20 to 60 parts.

[0019] In step (2), the temperature of the added deionized water is 10-30°C.

[0020] This invention utilizes low molecular weight lignin to partially replace polyester diols to synthesize biodegradable lignin-based waterborne polyurethane, and introduces a small amount of hydrophobic polydimethylsiloxane segments to improve the hydrophobic and antifouling properties of the polyurethane coating. Based on the high reactivity and multi-hydroxyl structure of low molecular weight lignin, the prepared waterborne polyurethane possesses a three-dimensional network cross-linked structure. Simultaneously, strong hydrogen bonds are formed between the lignin molecules and the polyurethane matrix, resulting in waterborne polyurethane with excellent mechanical properties; its tensile strength and elongation at break exceed 25 MPa and 700%, respectively. When the above-mentioned lignin-based waterborne polyurethane emulsion is coated onto the surface of paper, the paper acquires hydrophobic and oil-resistant properties. After immersing it in water for 1 hour, its mechanical strength still retains more than 70%; when filled with edible oil at 100°C, no leakage occurs after 0.5 hours.

[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0022] 1. This invention uses highly reactive low molecular weight lignin to synthesize waterborne polyurethane. There is good compatibility and strong hydrogen bonding between lignin and polyurethane matrix, and lignin also acts as a crosslinking agent. Therefore, waterborne polyurethane with excellent mechanical properties is obtained.

[0023] 2. The polyester diol and lignin used in this invention are both biodegradable raw materials, and the prepared waterborne polyurethane coating is a biodegradable material that is green and environmentally friendly and will not cause environmental pollution.

[0024] 3. Due to the large number of lignin molecules in the main chain of waterborne polyurethane, the prepared waterborne polyurethane has good adhesion to the paper surface; the cross-linking structure and hydrophobic segments of lignin-based waterborne polyurethane enable the paper to obtain excellent hydrophobic and oil-resistant properties. Detailed Implementation

[0025] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.

[0026] Unless otherwise specified in the embodiments of this invention, the conditions shall be performed according to conventional conditions or conditions recommended by the manufacturer. All raw materials and reagents used, unless otherwise specified, are commercially available conventional products.

[0027] The low molecular weight lignin used in the following examples and comparative examples was obtained by extraction from industrial alkali lignin using anhydrous ethanol. The specific characteristic parameters of both are shown in Table 1. Low molecular weight lignin has a low molecular weight and a high hydroxyl content, and is completely soluble in acetone, exhibiting higher reactivity, which is beneficial for the synthesis of polyurethane.

[0028] In the following examples and comparative examples, the total mass of lignin and polyester diol was 100 parts, the number average molecular weight of the polyester diol used was 2000 g / mol, the catalyst used was dibutyltin dilaurate (DBTDL), and the isocyanate index R was controlled to be 1.1 during the reaction.

[0029] Unless otherwise specified, the parts in the following examples and comparative examples refer to parts by mass, and 1 part by mass means 1g.

[0030] Table 1. Characteristic parameters of industrial alkali lignin and low molecular weight lignin

[0031]

[0032] Example 1

[0033] (1) 80 parts PCL and 2 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 34.6 parts IPDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0034] (2) Transfer the above system to an emulsifier, add deionized water at a speed of 1500 r / min, control the solid content to 35 wt%, continue stirring for 5 minutes after emulsification, then adjust the speed to 500 r / min and continue stirring for 1 hour; perform vacuum distillation on the emulsified sample at 50℃ and a vacuum degree of less than -0.09 MPa to remove acetone and obtain the desired lignin-based waterborne polyurethane emulsion.

[0035] Example 2

[0036] (1) 80 parts PCL and 5 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 35 parts IPDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0037] (2) Same as Example 1.

[0038] Example 3

[0039] (1) 80 parts of PCL and 10 parts of hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 35.6 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts of low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts of acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts of triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0040] (2) Same as Example 1.

[0041] Example 4

[0042] (1) 80 parts of PCL and 5 parts of dihydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 35.6 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts of low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts of acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts of triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0043] (2) Same as Example 1.

[0044] Example 5

[0045] (1) 90 parts PCL and 5 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 29.4 parts IPDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 10 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 60 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0046] (2) Same as Example 1.

[0047] Example 6

[0048] (1) 70 parts PCL and 5 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 40.5 parts IPDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 30 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 20 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0049] (2) Same as Example 1.

[0050] Example 7

[0051] (1) 80 parts PLA and 5 parts monohydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 35 parts IPDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0052] (2) Same as Example 1.

[0053] Example 8

[0054] (1) 80 parts of poly(lactide-co-caprolactone) diol and 5 parts of hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 35 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts of low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts of acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts of triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0055] (2) Same as Example 1.

[0056] Example 9

[0057] (1) 80 parts PCL and 5 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 33.9 parts IPDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMBA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.1 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0058] (2) Same as Example 1.

[0059] Example 10

[0060] (1) 80 parts PCL and 5 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 26.4 parts HDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMBA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0061] (2) Same as Example 1.

[0062] Example 11

[0063] (1) 80 parts PCL and 5 parts single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 39.4 parts MDI and 0.4 parts DBTDL were added and reacted for 2 hours. Then, 6 parts DMBA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts acetone were added. After the reaction, the temperature was lowered to room temperature, 4.5 parts triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0064] (2) Same as Example 1.

[0065] Comparative Example 1 (without added lignin)

[0066] (1) 100 parts of PCL and 5 parts of hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 23.8 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. During the reaction, 40 parts of acetone were added. After the reaction was completed, the temperature was lowered to room temperature and 4.5 parts of triethylamine were added and stirred for 0.5 hours. The isocyanate index R was 1.1.

[0067] (2) Same as Example 1.

[0068] Comparative Example 2 (without hydrophobic modifier)

[0069] (1) 80 parts of PCL were added to the reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 34.3 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts of low molecular weight lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts of acetone were added. After the reaction was completed, the temperature was lowered to room temperature, 4.5 parts of triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0070] (2) Same as Example 1.

[0071] Comparative Example 3 (using industrial alkali lignin)

[0072] (1) 80 parts of PCL and 5 parts of single-hydroxyl-terminated polydimethylsiloxane were added to a reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 31 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. 20 parts of industrial alkali lignin were dissolved in acetone (20 wt%) and added to the system and reacted for 4 hours. During the reaction, 40 parts of acetone were added. After the reaction was completed, the temperature was lowered to room temperature, 4.5 parts of triethylamine were added, and the mixture was stirred for 0.5 hours. The isocyanate index R was 1.1.

[0073] (2) Same as Example 1.

[0074] Because industrial alkali lignin cannot be completely dissolved in acetone, the resulting waterborne polyurethane emulsion contains undissolved lignin particles, resulting in incomplete reaction, poor emulsification, and difficulty in use.

[0075] Comparative Example 4 (without hydrophobic modifier and lignin)

[0076] (1) 100 parts of PCL were added to the reactor and dehydrated under vacuum at 110°C, then cooled to 70°C. Under nitrogen protection, 23.2 parts of IPDI and 0.4 parts of DBTDL were added and reacted for 2 hours. Then, 6 parts of DMPA were dissolved in DMF (25 wt%) and added to the system and reacted for 1 hour. During the reaction, 40 parts of acetone were added. After the reaction was completed, the temperature was lowered to room temperature, and 4.5 parts of triethylamine were added and stirred for 0.5 hours. The isocyanate index R was 1.1.

[0077] (2) Same as Example 1.

[0078] The aqueous polyurethane emulsions from the examples and comparative examples were cast into polytetrafluoroethylene molds and cured into polyurethane films. Their mechanical properties (GB / T 528-2009) and water contact angles were tested, and the results are shown in Table 2. The aqueous polyurethanes prepared from low molecular weight lignin (Examples 1-6, Comparative Example 2) exhibited excellent mechanical properties, with tensile strengths all exceeding 25 MPa and elongation at break exceeding 700%. Comparative Example 1, without the addition of low molecular weight lignin, had a tensile strength of only 9.4 MPa, indicating that the crosslinking effect of low molecular weight lignin enhanced the mechanical properties of the aqueous polyurethane. Regarding hydrophobic properties, samples from Comparative Examples 2 and 4, without the addition of hydrophobic modifiers, had small water contact angles and strong hydrophilicity. The addition of low molecular weight lignin slightly improved the hydrophobic properties. After the addition of hydrophobic modifiers, the hydrophobic properties of the lignin-based aqueous polyurethanes were significantly improved, and the water contact angle increased with the increase of the hydrophobic modifier (Examples 1-3). Therefore, the prepared lignin-based waterborne polyurethane has excellent mechanical and hydrophobic properties.

[0079] Table 2 Mechanical properties and hydrophobicity of lignin-based waterborne polyurethane

[0080] 1 30.7±2.4 884±41 89.8±2.2 2 40.3±1.1 1148±34 100.8±1.5 3 34.3±1.8 1053±35 103.6±1.8 4 33.8±1.7 1063±64 102.5±2.0 6 25.2±1.2 740±35 100.2±1.6 Comparative Example 1 9.4±0.3 1005±33 101.2±1.3 Comparative Example 2 31.3±1.5 756±20 55.9±1.6 Comparative Example 3 12.5±0.8 523±18 52.3±2.4 Comparative Example 4 10.0±0.5 963±25 47.6±1.6

[0081] The aqueous polyurethane emulsions used in the examples and comparative examples were coated onto the surface of kraft paper at an application rate of 16 g / m². 2 The paper was dried in a 50℃ oven for 0.5 hours, and its water contact angle, water absorption (GB / T1540-2002), and grease resistance (GB / T22805.2-2008) were tested. The results are shown in Table 3. Kraft paper has very poor water and grease resistance. After being coated with a water-based polyurethane coating, its water and grease resistance were significantly improved. A comparison of the examples and comparative examples revealed that this was mainly due to the cross-linking effect of lignin and the hydrophobicity of the hydrophobic modifier.

[0082] Table 3 Properties of paper coated with lignin-based waterborne polyurethane

[0083] Kraft paper 15.2±1.3 70.87±2.24 1 1 92.3±1.2 1.62±0.23 12 2 102.5±1.8 1.50±0.10 12 3 105.3±1.6 1.30±0.10 12 4 103.7±2.2 1.28±0.15 12 6 102.6±1.9 1.85±0.16 12 Comparative Example 1 101.8±1.3 2.31±0.21 7 Comparative Example 2 60.2±2.5 2.03±0.18 12 Comparative Example 3 54.6±1.8 2.93±0.26 8 Comparative Example 4 50.3±1.4 2.72±0.28 6

[0084] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. The application of a hydrophobic, oil-resistant, and biodegradable lignin-based waterborne polyurethane in paper coating, characterized in that, The waterborne polyurethane comprises, by weight: 70-90 parts polyester diol, 10-30 parts low molecular weight lignin, 1-10 parts hydrophobic modifier, 25-50 parts isocyanate, 4-8 parts anionic hydrophilic chain extender, 0.2-0.6 parts catalyst, and 3-6 parts neutralizer; wherein the total amount of polyester polyol and low molecular weight lignin is 100 parts, and the isocyanate index R is 1.0-1.

2. The weight-average molecular weight of the low molecular weight lignin is 800~1500 g / mol; The polyester diol is at least one of polycaprolactone diol and poly(lactide-co-caprolactone) diol; The hydrophobic modifier is at least one of the following: dihydroxyl-terminated polydimethylsiloxane, unihydroxyl-terminated polydimethylsiloxane, and unihydroxyl-terminated polydimethylsiloxane.

2. The application according to claim 1, characterized in that, The number-average molecular weight of the polyester diol is 500~5000 g / mol.

3. The application according to claim 1, characterized in that, The low molecular weight lignin is obtained by extraction with ethanol, acetone or ethyl acetate using industrial lignin with a weight average molecular weight of 3000~6000 g / mol as raw material.

4. The application according to claim 1, characterized in that, The number average molecular weight of the hydrophobic modifier is 1000~5000 g / mol.

5. The application according to claim 1, characterized in that, The isocyanate is at least one of isophorone diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, and toluene diisocyanate.

6. The application according to claim 1, characterized in that, The anionic hydrophilic chain extender is at least one of 2,2-dimethylolpropionic acid and 2,2-dimethylolbutyric acid.

7. The application according to claim 1, characterized in that, The catalyst is an organotin catalyst; the neutralizing agent is at least one of triethylamine and ammonia.

8. The application according to any one of claims 1 to 7, characterized in that, The method for preparing the waterborne polyurethane is characterized by comprising the following steps: (1) After dehydrating the polyester diol and hydrophobic modifier under vacuum at 110±10℃, the temperature is lowered to 70~90℃; under nitrogen protection, isocyanate and catalyst are added and reacted for 1~2 hours; then anionic hydrophilic chain extender is added and reacted for 1~2 hours; low molecular weight lignin is added and reacted for 2~5 hours. Acetone is added during the reaction to reduce the viscosity of the system; after the reaction is completed, the temperature is lowered to room temperature, a neutralizing agent is added, and the mixture is stirred for 0.5~1 hours. (2) Add deionized water to the above system at a speed of 1000~2000 r / min, control the solid content of the emulsion to be 20~45 wt%, continue stirring for 5~10 minutes after emulsification, and then adjust the speed to 300~500 r / min and continue stirring for 0.5~1 hour; perform vacuum distillation on the emulsified sample at 40~60℃ and vacuum degree less than -0.09 MPa to remove acetone and obtain the lignin-based waterborne polyurethane.

9. The application according to claim 8, characterized in that, The anionic hydrophilic chain extender is added in solution form at a concentration of 20-30 wt%, and the solvent is one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide. The low molecular weight lignin is added in the form of a solution with a concentration of 10-30 wt% and acetone as the solvent.

10. The application according to claim 8, characterized in that, In step (1), the amount of acetone added during the reaction is 20-60 parts; In step (2), the temperature of the added deionized water is 10~30℃.

Citation Information

Patent Citations

  • Styrene-butadiene-diphenyl polymer latex and application thereof

    CN114901707A

  • Polyacrylic emulsion as well as preparation method and application thereof

    CN116265502A

  • Preparation method and application of full-bio-based oil-proof hydrophobic paper surface coating

    CN116856196A